2020
DOI: 10.1080/10872981.2020.1780697
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a collaborative medicine and pharmacy educational activity in two countries

Abstract: Background: To promote better collaboration for patient care, interprofessional education (IPE) is required in many health professions courses. However, successful IPE implementation at scale can be challenging because of complicated logistics and competing priorities. Implementing across multiple geographies adds further complexity. Objective: This paper describes the implementation of a full cohort IPE activity for medical and pharmacy students delivered at both the Australian and Malaysian campuses of Monas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
7
1
7
Order By: Relevance
“…The comprehensive curricular changes to why, what, and how we teach pharmacy students have been transformational and sustained. We have used some of these models (e.g., DEAR, skills coaching) to inform the redesign of our Bachelor of Pharmaceutical Sciences program and collaborative work with other health professions [44]. When faced with a need to convert quickly to online instruction in response to the COVID-19 pandemic, our faculty was able to work together effectively, in part because of the trust built through creating this new program [44,55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The comprehensive curricular changes to why, what, and how we teach pharmacy students have been transformational and sustained. We have used some of these models (e.g., DEAR, skills coaching) to inform the redesign of our Bachelor of Pharmaceutical Sciences program and collaborative work with other health professions [44]. When faced with a need to convert quickly to online instruction in response to the COVID-19 pandemic, our faculty was able to work together effectively, in part because of the trust built through creating this new program [44,55].…”
Section: Discussionmentioning
confidence: 99%
“…We have used some of these models (e.g., DEAR, skills coaching) to inform the redesign of our Bachelor of Pharmaceutical Sciences program and collaborative work with other health professions [44]. When faced with a need to convert quickly to online instruction in response to the COVID-19 pandemic, our faculty was able to work together effectively, in part because of the trust built through creating this new program [44,55]. We hope that sharing our systems, processes, and resources can assist others looking to undertake a transformational health curriculum rebuild.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other opportunities for IPE integration include partnering with nurses in allergy immunotherapy instruction or including pharmacists as instructors when teaching A/I trainees in inpatient settings. At the undergraduate level, Brock et al 25 described an interactive, blended 150-minute IP learning experience for medical and pharmacy students focusing on asthma management. It was delivered online in 2 countries (Australia and Malaysia) by the medicine and pharmacy faculty.…”
Section: Integrating Interprofessional Educationmentioning
confidence: 99%
“…Reports of IPE activities are predominantly from developed countries, with developing countries such as Malaysia incorporating IPE into healthcare education curricula more recently [ 86 – 89 ]. Brock et al recently reported on the development of an IPE activity for medical and pharmacy students at Monash University, delivered on their Australian and Malaysian campuses [ 90 ]. They note the importance of developing context-specific activities, consistent with recommendations from studies that have incorporated Western IPE competency frameworks into South East Asian healthcare education curricula [ 91 , 92 ].…”
Section: Translating Newcastle University’s Mbbs Curriculum Into the Malaysian Contextmentioning
confidence: 99%